2016
DOI: 10.1175/waf-d-16-0041.1
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategies of an Hourly Update 3DVAR Data Assimilation System for Improved Convective Forecasting

Abstract: This study examines two strategies for improving the analysis of an hourly update three-dimensional variational data assimilation (3DVAR) system and the subsequent quantitative precipitation forecast (QPF). The first strategy is to assimilate synoptic and radar observations in different steps. This strategy aims to extract both large-scale and convective-scale information from observations typically representing different scales. The second strategy is to add a divergence constraint to the momentum variables i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…The LSC is only applied to the 3‐hourly cycle at each update cycle on the inner domain. The use of two RUCs allows large‐scale and small‐scale information being treated separately and optimally, which is consistent with the principle of multistep DA in recent studies (Ha & Lee, ; Tong et al, ).…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…The LSC is only applied to the 3‐hourly cycle at each update cycle on the inner domain. The use of two RUCs allows large‐scale and small‐scale information being treated separately and optimally, which is consistent with the principle of multistep DA in recent studies (Ha & Lee, ; Tong et al, ).…”
Section: Methodssupporting
confidence: 75%
“…Several studies (Li et al, ; Peng et al, ; Xie et al, ) introduced methods to retain the large‐scale information during DA of high‐resolution observations based on the principle of scale separation and optimization. Although the application of these methods (J. Gao et al, ; Ha & Lee, ; Tong et al, ) showed improved analysis fields and precipitation forecasts in real cases, their effect in improving large‐scale analysis is still limited due to the sparseness of large‐scale observations and the inherent shortcomings associated with lateral boundary conditions in LAMs.…”
Section: Introductionmentioning
confidence: 99%
“…The indirect radar DA approach of Wang et al (2013) was used for radar reflectivity, in which retrieved hydrometer mixing ratios were assimilated. The two-step procedure of Tong et al (2016) was also used to reduce analysis noise in radar DA, via the use of a shorter length scale and analysis cycle. The system was examined by comparing experimental forecast results, i.e., using 3DVar and hybrid experiments without (Exp3DVC and ExpHYBC) and with radar DA (Exp3DVCR and ExpHYBCR).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, verification against radiosondes and METAR observations (see Figure 4) were also performed for all experiments. The radar DA experiments followed the two-step procedure of Tong et al (2016), as shown in Figure 5. In Step 1, the first assimilation cycle was initiated at 12:00 UTC on 6 August 2016 with GTS, with radiosonde, surface network and aircraft data assimilated.…”
Section: Experiments Design and Verification Methodsmentioning
confidence: 99%
See 1 more Smart Citation